Baseline Characteristics of Participants in the ASPREE (Aspirin in Reducing Events in the Elderly) Study - McNeil, J.; Woods, R.; Nelson, M.; Murray, A.; Reid, Christopher; Kirpach, B.; Storey, E.; Shah, R.; Wolfe, R.; Tonkin, A.; Newman, A.; Williamson, J.; et al. (2019)
This is a correction to: The Journals of Gerontology: Series A, Volume 72, Issue 11, November 2017, Pages 1586–1593, https://doi.org/10.1093/gerona/glw342